UPAYA MENINGKATKAN PENGUASAAN MUFRODAT BAHASA ARAB DENGAN MEDIA FLASHCARD di SDI ULUL ALBAB BLARU BADAS - luthfi, ibnu mas ud Luthfi (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2025)
Arabic is a foreign language that has features and characteristics that are different from other languages. The most basic thing you need to learn in Arabic is vocabulary. In learning vocabulary, educators should teach things that are appropriate to the context so that they are easy to apply both orally and in writing by students. Through the application of Arabic flashcard media, it is hoped that it will be able to help students recognize, understand and memorize Arabic vocabulary. The implementation of Arabic flashcard learning media was carried out at SDI Ulul Albab Batan Blaru, Kediri. The results show that Arabic Flashcard Media which is packaged with interesting and innovative material can increase the Arabic vocabulary of SDI ULUL ALBAB Students Keywords: Arabic, Vocabulary, Flashcard Media